Prediction of laparoscopic procedure duration using unlabeled, multimodal sensor data - Bodenstedt, Sebastian; Wagner, Martin; Kenngott, Hannes Götz; Müller, Beat P. (International journal of computer assisted radiology and surgery, 2019)
Purpose The course of surgical procedures is often unpredictable, making it difficult to estimate the duration of procedures beforehand. This uncertainty makes scheduling surgical procedures a...